The Mother Knot - Lazarre, Jane (Book collections on Project MUSE., 1997)
In this compelling memoir by a writer, mother, and feminist, Jane Lazarre confronts the myth of the "good mother" with her fiercely honest and intimate portrait of early motherhood as a time of profound ambivalence and upheaval, filled with desperation as well as joy, the struggle to reclaim a sense of self, and sheer physical exhaustion. Originally published in 1976, The Mother Knot is a feminist classic, as relevant today as it was twenty years ago.